Body composition responses to 12 weeks of training on various modes of home exercise equipment in sedentary adults - Eber, Teresa S. (My University, 1996)
This study compared body composition responses as a result of 12 weeks of training on various home exercise equipment. Ninety-four sedentary adults ranging in age from 23 to 49 years were randomly assigned to 1 of 5 groups: stationary bicycle (B = 19); crosscountry ski simulator (XC = 22); motorized treadmill (T = 21); hydraulic stepper (S = 15); or control (C = 17). Data collected on subjects included various circumference measurements and body composition before and after the training. Experimental groups trained 3 days a week, 30-45 min per day, at 8 1.1 - 87.1 % HRmax. Triceps measurement were significantly (p < .05) decreased in the male B group, and the female B, XC, and T groups from pre-to posttest. The male B and XC groups significantly (p < .05) decreased chest measurements. Waist measurements were significantly (p < .05) decreased in the male B, XC, and T groups, and female B and XC groups. All exercise groups excluding the female B group significantly (p < .05) decreased hip circumferences. Thigh circumferences were not significantly (p < .05) altered in any of the experimental groups. Subject weight was significantly (p < .05) decreased in the B, XC, and T groups for both males and females. Males significantly (p < .05) decreased percent body fat by 8.1% (26.0 to 23.9) in the B group. 10.3% (28.1 to 25.2) in the XC group. 10.2% (27.4 to 24.6) in the T group, and 9.0% (25.6 to 23.3) in the S group. Females significantly (p < .05) decreased percent body fat 4.7% (38.0 to 36.2) in the B group, 6.6% (33.2 to 3 1 .O) in the XC group, and 4.6% (35.1 to 33.5) in the T group. All male experimental groups were significantly (p < .05) different from the C group. There was no significant (p > .05) difference detected between the female groups.
Keywords: Human body - Composition; Exercise - Equipment and supplies; Exercise - Physiological aspects